Uptake of hepatitis C direct-acting antiviral treatment in China: a retrospective study from 2017 to 2021 - Xinyu Du; Jiarun Mi; Hanchao Cheng; Yuanyuan Song; Yuchang Li; Jing Sun; Polin Chan; Zhongdan Chen; Simon Luo (BMC, 2023)
Abstract Background Direct-acting antivirals (DAAs) for hepatitis C treatment in China became available since 2017. This study expects to generate evidence to inform decision-making in a nationwide scale-up of DAA treatment in China. Methods We described the number of standard DAA treatment at both national and provincial levels in China from 2017 to 2021 based on the China Hospital Pharmacy Audit (CHPA) data. We performed interrupted time series analysis to estimate the level and trend changes of the monthly number of standard DAA treatment at national level. We also adopted the latent class trajectory model (LCTM) to form clusters of the provincial-level administrative divisions (PLADs) with similar levels and trends of number of treatment, and to explore the potential enablers of the scale-up of DAA treatment at provincial level. Results The number of 3-month standard DAA treatment at national level increased from 104 in the last two quarters of 2017 to 49,592 in the year of 2021. The estimated DAA treatment rates in China were 1.9% and 0.7% in 2020 and 2021, which is far below the global target of 80%. The national price negotiation at the end of 2019 resulted in DAA inclusion by the national health insurance in January 2020. In that month, the number of treatment increased 3668 person-times (P < 0.05). LCTM fits the best when the number of trajectory class is four. PLADs as Tianjin, Shanghai and Zhejiang that had piloted DAA price negotiations before the national negotiation and that had explored integration of hepatitis service delivery with prevention and control programme of hepatitis C within the existing services demonstrated earlier and faster scale-up of treatment. Conclusions Central negotiations to reduce prices of DAAs resulted in inclusion of DAA treatment under the universal health insurance, which are critical elements that support scaling up access to hepatitis C treatment in China. However, the current treatment rates are still far below the global target. Targeting the PLADs lagged behind through raising public awareness, strengthening capacity of the healthcare providers by roving training, and integrate prevention, screening, diagnosis, treatment and follow-up management of hepatitis C into the existing services are needed.